(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the importance of cooperation between the public and private sectors in diversifying the income of the population. The need for joint activities of the public and private sectors is indicated in order to ensure economic stability and ensure that the population has different sources of income. The article examines the role of the private sector in economic growth, its important role in attracting investments, and effective ways to diversify the income of the population through mechanisms such as public-private sector partnership (PPP). Important factors are also noted as the strategic policies of the state and the innovative approaches of the private sector to ensure social stability, create jobs and improve equality in the distribution of income. The article highlights the importance of effective cooperation between the public and private sectors to achieve economic and social stability.